Potential Treponema denticola-based periodontal vaccine to resolve a global public health challenge: a narrative literature review. (4th May 2022) - Mirmohammadsadegh, Navid; Mashreghi Mohammadi, Neshaut; Amin, Mohsen
ABSTRACT: Introduction: Periodontitis is a diseased condition of the gum which imposes considerable costs on healthcare systems. It progresses further beyond the inflammation of supportive tissues of the teeth, and the collateral damages are closely associated with Alzheimer's disease, cardiovascular disease, and diabetes mellitus. Areas covered: A comprehensive literature review was performed to summarize published studies in English during the period of 1990–2021 to discuss the rationales for developing periodontal vaccine, cost-effectiveness analyses on the prevention of periodontitis, Treponema denticola -based vaccine candidates, as well as immunological mechanisms in animal models. Expert opinion: Preventive strategies against periodontitis may halt the onset of gum inflammation and the consequent chronic diseases. Considering the multi-microbial condition of periodontitis, an ideal periodontal vaccine should target multiple pathological pathways. Preventive approaches compared to surgical treatments evidently have significant impact on the healthcare budget and long-term health of the individuals in different communities. Despite many advances in periodontal vaccine research, there are still significant hurdles to overcome in developing a vaccine. Investment in research and development activities on key periodontal pathogens including Treponema denticola and Porphyromonas gingivalis in the foreseeable future is a worthy and cost-effective approach for the policymakers to prevent deleterious impacts of periodontitis.